Design and Performance Evaluation of a Feed Distribution Device in the Small-Scale Pneumatic Conveying Feeder for Recirculating Aquaculture Systems - Liang Wang; Mingdong Ji; Kang Wu; Xudong Weng; Haijun Li (Fishes, 2025)
Due to its good adaptability, the pneumatic conveying feeder has been widely developed and applied in recirculating aquaculture systems (RASs). Its important performances include the integrity of feed pellets and the feeding accuracy. The aim of this study was to design and evaluate a feed distribution device for a small-scale pneumatic conveying feeder. A cylindrical hopper with a feed capacity of 4 kg and a feed distribution device were designed based on theoretical calculations. The motion and force of feed pellets during the distribution process were studied using the discrete element method (DEM) simulation to evaluate the integrity of feed pellets. Additionally, to evaluate feeding accuracy, the effect of discharge disk rotational speed on single feeding quantity was studied using DEM simulations and experimental validations, as well as the effect of the proportion of feed pellets in the hopper. Results showed that the maximum force on feed pellets was 1.25 N during the distribution process. It was inferred that the feed pellets can be distributed without breaking based on their shear strength. When the rotational speed of the discharge disk was set at a maximum of 28 rpm, the relative error of single feeding quantity between simulation and actual experiments was 4.43%, and the single feeding mass was 62.74 g, suggesting an optimal speed. In addition, the average single feeding quantity ranged from 262 to 301 feed pellets at the different proportions of feed pellets in the hopper, and its coefficient of variation was 12.46%, which generally meets the distribution requirements of the small-scale feeder. This study provides a feed distribution device for a small-scale pneumatic conveying feeder and offers references for the relevant analysis of DEM simulation.